PROCEDURAL ASPECTS OF GENERATION AND IMPLEMENTATION OF STRATEGIES FOR MANAGING SALES ACTIVITIES OF PROCESSING ENTERPRISES - Сергій Волик (Економіка та суспільство, 2024)
The article is devoted to developing conceptual foundations and procedures for generating and implementing strategies for managing the sales activities of processing enterprises. The study substantiates a model for the formation of the strategy of a processing enterprise, covering the key stages of strategic planning. It is recommended that the strategic marketing planning process be reviewed to ensure efficiency in the sales activities of processing enterprises. A strategic set of processing enterprises has been defined and characterized, which is a system of strategies of various types that are developed by an enterprise for a certain period, which reflects the specifics of the functioning and development of the enterprise, as well as the level of its claim to a place and role in the external environment. In order to introduce the most effective tools of strategic planning in the sales activities of a processing enterprise, a revision of the strategic marketing planning process is proposed. The main stages of marketing strategic planning of processing enterprises are the formation of the mission, the transformation of the mission into goals, the analysis of the external and internal environment, the conduct of SWOT analysis, the definition of marketing goals, the formation of marketing strategies, the development of a marketing program, the organization and implementation of marketing, as well as marketing control. Thanks to these milestones, the company can formulate its mission and goals and develop effective strategies and programs to achieve these goals. The basic principles of forming a strategic set are emphasized, considering the orientation towards the ultimate goals, the balance of strategies, and clarity in understanding the need for their application. Strategic priorities for increasing the competitiveness of processing enterprises have been identified, such as increasing the concentration of capital, investment attractiveness, reinvestment of profits, increasing the size of enterprises, and introducing innovations. Implementing these strategies should contribute to increasing economic efficiency and adapting to the challenges of sales markets.